Let's denote x inverse as a and y inverse as b.
From the equations:
2a - 3b = 4
4a + b = 1
Rearranging the equations:
2a - 3b = 4 --> 2a = 4 + 3b --> a = 2 + 3/2 * b
4a + b = 1 --> 4a = 1 - b --> a = 1/4 - 1/4 * b
Now equating the two expressions for a:
2 + 3/2 * b = 1/4 - 1/4 * b
Multiplying each by 4 to get rid of the fractions:
8 + 6b = 1 - b
Adding b to both sides:
7b + 8 = 1
Subtracting 8 from both sides:
7b = -7
Divide by 7:
b = -1
Now that we have b, substitute it back into one of the original equations to solve for a. Using the second equation:
4a + (-1) = 1
4a = 2
a = 2/4
a = 1/2
Therefore, x inverse (a) = 1/2 and y inverse (b) = -1.
Solve 2x inverse - 3y inverse= 4
4x inverse+ y inverse = 1
1 answer